Whipple’s Disease, One of Medicine’s Great Imitators: A Case Report - Francesca Heard; Elizabeth Hart; Vicki Fleming; Claudia Santos; Ross Thomson (European Medical Journal)
The authors describe a rare case of a 46-year-old woman, presenting with a 1-year history of a wasting disease and widespread mediastinal lymphadenopathy on imaging. The patient had a history of pulmonary hypertension diagnosed 7 years prior and had been treated with macitentan (an endothelin receptor antagonist) and sildenafil. Following an admission to the authors’ centre with severe anaemia and workup for suspected haematological malignancy, duodenal biopsy confirmed the diagnosis of Whipple’s disease. Interestingly, the patient did not report the cardinal symptoms of arthralgia, fevers, or gastrointestinal upset, emphasising the importance of investigating for Whipple’s disease even in the absence of these symptoms, particularly in the context of malabsorption or chronic wasting disease. Whipple’s disease can be regarded as a ‘great imitator’, often with non-specific signs and symptoms, which can present a diagnostic challenge. Following diagnosis, appropriate antibiotic therapy was commenced, and the patient made a complete clinical recovery, including resolution of pulmonary arterial hypertension, which likely was the presenting feature of this case of Whipple’s Disease, a rare phenomenon associated with this infection.